Determination of optimum heat transfer area for vacuum evaporators in ships - Ozturk, R; Alkan, AD (SOC NAVAL ARCHITECTS & MARINE ENGINEERS, 2004)
In ships, utility water can be produced from seawater through a vacuum evaporator instead of supplying from ports, and this solution will certainly allow extra load capacity for ships. In this application, the size of vacuum evaporators and their heat transfer areas are significant factors in terms of investment costs and the volume or weight capacity, which for ships are particularly important parameters. In the present research, the change of heat transfer areas of vacuum evaporators that are used to produce utility water was analyzed with respect to design parameters and the results from the thermodynamic analysis were evaluated to define the optimum heat transfer area. Because an analytical method has been employed in the definition of the optimum heat transfer area, the influence of design parameters on the evaporator size can be identified easily.
Keywords: Engineering; Oceanography